SUPPLY CHAIN MANAGEMENT STRATEGIES AND CUSTOMERS’ VALUE IN SKYRUN INTERNATIONAL, CROSS RIVER STATE, NIGERIA (Journal of the Management Sciences, 2025)
This study examined supply chain management strategies and customers’ value in Skyrun International, Cross River State. It aimed to determine the relationship between supply chain management strategies – logistics, inventory and supplier relationship management and customers’ value in Skyrun International. Cross-sectional survey research design was adopted. Primary data were elicited from 168 executive and managerial personnel at Skyrun International, Calabar using a structured questionnaire. The data obtained were descriptively analyzed and interpreted while hypotheses testing was done using Pearson’s product moment correlation. The findings of the study revealed that logistics management, inventory management and supplier relationship management had significant positive relationships with customers’ value in Skyrun International, Calabar. Hence, it was recommended that manufacturers of consumer electronics should prioritize logistics management by ensuring efficient procurement, transportation capacity, and warehouse optimization to guarantee uninterrupted processes that create customer value. Additionally, inventory resources should be strategically managed by a designated department to maintain consistent availability of raw materials, work-in-progress accuracy, and finished goods audits, thereby enhancing customer value.
Keywords: Supply Chain Management; Customer Satisfaction; Logistics Management; Inventory Management; Supplier Relationship Management